Current trends in surgical approach and outcomes following pituitary tumor resection. (13th January 2015) - Villwock, Jennifer A.; Villwock, Mark R.; Goyal, Parul; Deshaies, Eric M.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The goals of pituitary tumor resection include normalizing endocrine function, relieving mass effect, and minimizing risk of recurrence. This study investigated current trends in costs and complications for transfrontal and transsphenoidal pituitary surgery. Study Design Retrospective review of the 2008–2011 Nationwide Inpatient Sample for patients undergoing pituitary lesion resection. Methods Demographics and outcomes were compared between transfrontal and transsphenoidal surgical approaches using χ2 tests. Multivariate analysis was performed to investigate outcomes while controlling for confounders. Results There were 8, 543 admissions for resection of pituitary lesions that met our inclusion criteria. Most (>90%) were treated transsphenoidally. The transfrontal approach was most frequent in the young (<35 years) and in the South. Rates of mortality and complications were higher in patients undergoing transfrontal surgery. Multivariate analysis found transsphenoidal resection was associated with a reduction in hospital costs and length of stay by over 50%; low‐volume hospitals had increased cost and length of stay. There was an increased rate of transfrontal approaches at low‐volume centers. Conclusions Multiple factors influence outcomes of pituitary tumor resection. Transsphenoidal pituitary surgery is associated with a shorter length of stay, lower cost, and lower complication rates when compared to transfrontal surgery. Case specifics, including tumor location and size, influence approach and lead to a selection bias that cannot be controlled for in the present study. The prevalence of transfrontal resections at low‐volume centers may indicate an area of further investigation. Additionally, when controlling for surgical approach, low‐volume centers were found to adversely affect economic outcomes and also warrants investigation. Level of Evidence 2c. Laryngoscope, 125:1307–1312, 2015